Fundamentals of total quality safety management and auditing - Austin, Jacinta (Arcler Press, 2017)
"Total Quality Management (TQM) is a business philosophy that yields customer satisfaction and continuous process improvement. This book discusses a series of fundamentals for creating an operationally excellent management system (OEMS). The text also focuses on the ISO-9000 Quality Program, Voluntary Protection Program, and Process Safety Management. For each of these topics, the key principles are identified and described, and the quality principles are adapted to safety"--Provided by publisher.